A national survey of pharmacists and interns in Aotearoa New Zealand: provision and views of extended services in community pharmacies - Janet McDonald; Caroline Morris; Megan Pledger; Phoebe Dunn; Ausaga Fa'asalele Tanuvasa; Kirsten Smiler; Jacqueline Cumming (BMC, 2021)
Abstract Background Changes in pharmacy models of care, services and funding have been occurring internationally, moving away from the traditional dispensing role to more extended patient-facing roles utilising pharmacists' clinical skills. This study aimed to identify the extended services offered by community pharmacy in Aotearoa New Zealand and the barriers and facilitators to extended services provision. The study is unique in that it includes intern (pre-registration) pharmacists. Methods An online survey, conducted in 2018, of all pharmacists and intern (pre-registration) pharmacists working in a community pharmacy. Data were analysed using descriptive statistics and regression analyses. Results The results are based on replies from 553 community pharmacists and 59 intern pharmacists (response rate: 19 and 26% respectively). Both pharmacists (83%) and interns (85%) want to work at the top of their scope of practice. Wide variation exists in the specific services individual pharmacists offer. Most pharmacists were accredited to supply the emergency contraceptive pill (95%), sildenafil for erectile dysfunction (86%) and trimethoprim for uncomplicated urinary tract infection (85%). Fewer were able to immunise (34%) or to supply selected oral contraceptives (44%). Just under a quarter could provide a Medicines Use Review (MUR) or Community Pharmacy Anticoagulation Management Service (CPAMS). Of the pharmacists not already accredited, 85% intended to gain accreditation to supply selected oral contraceptives, 40% to become vaccinators, 37% to offer CPAMS and 30% MUR. Interns expressed strong interest in becoming accredited for all extended services. Poisson regression analyses showed key factors supporting the likelihood of providing extended services were owner and management support and appropriate space and equipment. Being excited about the opportunities in community pharmacy, having employer funding and time for training and sufficient support staff were also statistically significant. Conclusions Pharmacists need time and a supportive management structure to enable them to deliver extended services. Health policy with a greater strategic emphasis on funding services and pharmacist training, and developing technician support roles, will help to minimise or eliminate some of the barriers to role expansion both in Aotearoa New Zealand and internationally.